One Kairomone and Multiple Effects in Daphnia Species—5α-Cyprinol Sulfate Induces Morphological Defenses in the Invasive Species Daphnia lumholtzi - Hahn, Meike; von Elert, Eric (Frontiers in Ecology and Evolution, 2022)
Recently, the first chemical cues, which induce defenses in freshwater zooplankton of the genus Daphnia have been identified. Still it is unknown how general these so-called kairomones are and if they are perceived by and thereby benefitting invasive species. We here report the chemical identity of the fish-derived chemical signal that induces morphological defensive structures in the invasive species Daphnia lumholtzi. We used bioassay-guided isolation (LC-MS) of incubation water of fish and identified the bile salt 5α-cyprinol sulfate as the kairomone. We confirmed this finding by bioassays, in which D. lumholtzi was exposed to purified 5α-cyprinol sulfate from fish bile and showed that 10 pM 5α-cyprinol sulfate induces significantly elongated helmets and spines in relation to body length. These results identify on one hand another Daphnia species besides Daphnia magna, which is responding to this particular fish-borne kairomone, and on the other hand they reveal another defense that the kairomone induces besides DVM. Taken together a high evolutionary conservancy of the molecular mechanism behind inducible defenses in Daphnia spp. against fish can be deduced. It is reasonable to expect that 5α-cyprinol sulfate is involved in further predator - prey communication between Daphnia and fish, which may be of special ecological relevance with regard to invasive species as D. lumholtzi.